"I Did Not Miss Any, Only When I Had a Valid Reason": Accounting for Absences from Sociology Classes. (January 2015) - O'Sullivan, Sara; McMahon, Léan; Moore, Gemma; Nititham, Diane Sabenacio; Slevin, Amanda; Kelly, Christina; Wixted, Lisa
In this study we explore how absence from sociology classes is understood by undergraduate students at University College Dublin. The authors use Scott and Lyman's (1968) concept of accounts to explore absence sociologically. Drawing on data generated via focus groups, an open-ended questionnaire, and an online survey with students, we outline the different excuses and justifications for missing classes used by students and present their understanding of attendance at classes as an optional feature of student life. Individual students' attendance differed across courses, throwing doubt on the usefulness of individual-level frameworks for understanding attendance. We argue that decisions to attend are influenced by a variety of contextual issues, including knowledge of legitimate accounts for the setting, pedagogic approaches in use, and students' perceptions of the usefulness of classes. We conclude that to counter the trend of declining attendance and enhance student learning, it is important to better understand how both local norms, values, curriculum design, and assessment practices combine to facilitate students' absences. Focusing on accounts allows us to better understand student absence rather than accepting this as an inevitable feature of contemporary student behavior about which nothing much can be done.